Pengaruh Model Blended Learning terhadap Kemampuan Memecahkan Masalah Siswa pada Materi Faktor-Faktor yang Memengaruhi Laju Reaksi - Lucky Prima; Mustaji Mustaji; Andi Kristanto (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Interviews with Chemistry teachers at SMA Negeri 3 Surabaya showed several problems, including low student motivation and teachers' lack of understanding of Chemistry concepts. The experimental study used a quantitative approach with a quasi-nonequivalent pretest-posttest control group experimental design. The Lab Rotation type Blended Learning model significantly improves students' problem-solving abilities in reaction rate chemicals. The results of statistical analysis showed P Alpha of 0.014 < 0.05, and t count (t Stat) 2.53 > t table (t Critical two-tail) 2.00. In conclusion, there is a positive influence of the blended learning model on the problem-solving ability of students in Chemistry material at SMA Negeri 3 Surabaya.